RELAKSASI BENSON DAN TERAPI MUROTTAL SURAT AR-RAHMAAN MENURUNKAN KADAR GLUKOSA DARAH PUASA PADA PENDERITA DIABETES MELITUS TIPE 2 DI KECAMATAN MAOS - Esti Oktaviani Purwasih; Iman Permana; Yanuar Primanda (Jurnal Ilmiah Kesehatan Keperawatan, 2017)
Uncontrolled diabetes might generate the physical and psychological complication. The objective of this study was to analyze the effect of Benson’s relaxation and murottal “Ar-Rahmaan” to the fasting blood glucose (FBG) and stress score. This research was quasi experimental study with two group pre test-post test control group design. The research has been done  in the Health Care Center of Maos and “Graha Amanah” Clinic of Maos. Sample technique used total sampling, with 60 according to the inclusion criteria. The respondents were divided into control group and intervention group. Every group had 30 respondents. The intervention group was given Benson’s relaxation and murottal, menwhile the control group was given the Benson’s relaxation only. This intervention was done twice a day, in the morning and in the afternoon, for 7 days.The results showed the difference of the FBG level before and after intervention between groups (p value=0,000; Z score=- 4,097;Mean+SD intervention group= -66,300+45,672;Mean+SD control group= -23,766+13,438). Benson’s relaxation and murottal therapy could decrease FBG  significantly.